2005
DOI: 10.1016/j.polymer.2004.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the mechanical properties of nanoparticle/polymer composites

Abstract: A continuum-based elastic micromechanics model is developed for silica nanoparticle/polyimide composites with various nanoparticle/polyimide interfacial treatments. The model incorporates the molecular structures of the nanoparticle, polyimide, and interfacial regions, which are determined using a molecular modeling method that involves coarse-grained and reversemapping techniques. The micromechanics model includes an effective interface between the polyimide and nanoparticle with properties and dimensions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
258
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(268 citation statements)
references
References 24 publications
10
258
0
Order By: Relevance
“…Another mechanism that has been proposed [18,58] is the formation of an interphase or immobilised layer of polymer around the particles. Because the interparticle distance for nanocomposites is so small, then it is suggested that due to the proximity of the particles this interphase may be present throughout the entire polymer matrix.…”
Section: Immobilised Polymermentioning
confidence: 99%
“…Another mechanism that has been proposed [18,58] is the formation of an interphase or immobilised layer of polymer around the particles. Because the interparticle distance for nanocomposites is so small, then it is suggested that due to the proximity of the particles this interphase may be present throughout the entire polymer matrix.…”
Section: Immobilised Polymermentioning
confidence: 99%
“…Though the Mori-Tanaka model has been used widely to predict the elastic properties of two-phase composites, it is not expected to perform well in nano-scale level because the reinforcement and adjacent polymer region could not be accurately described as consisting of just two phases, i.e., fillers and matrix. To get rid of this drawback, an effective interface model was proposed [8]. This model considered a third phase between the nanoscale reinforcement and matrix, i.e., an effective interface.…”
Section: Representative Volume Element (Rve)mentioning
confidence: 99%
“…The Young's modulus of the fillers is 88.7 GPa. The effective particle volume fraction is 5%, and a constant effective interface thickness of 1.2 nm is adapted [8]. In order to confirm the usability of single particle model as a computationally efficient replacement of multi-particle unit cells, we carry out the simulations with unit cell with different particle amount (from 1 to 100) and random arrangements.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[36] However, as the inclusion size is decreased, the physicochemical properties of the interface must be taken into account for a correct prediction of observed moduli which display substantial dependence on inclusion size. [37] The dynamics observed at the interface is complex and depends both on size and stickiness of the NP. This will inevitably reflect on the mechanical properties.…”
Section: Distribution Of Chains Near Nanoparticle Surface -Effect Of mentioning
confidence: 99%